Magnetic graphene-based composite material for degrading dye and preparation method thereof

By using functionalized graphene oxide and thiolated core-shell particles in graphene-based composite materials, the problems of easy agglomeration and microbial invasion of nano-Fe3O4 are solved, and the antibacterial properties, adsorption properties and degradation properties of the material are significantly improved.

CN119633760AActive Publication Date: 2025-03-18SUZHOU INST OF TRADE & COMMERCE

Patent Information

Application Number
CN202411970616.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-18
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

In the prior art, nano-Fe3O4 is prone to agglomeration, resulting in uneven dispersion on the surface of graphene oxide. At the same time, microorganisms are prone to invade active adsorption sites during wastewater treatment, resulting in a decrease in the adsorption and degradation properties of graphene-based composite materials.

Method used

Functional graphene oxide and thiolated core-shell particles are used to prepare graphene-based composite materials that are magnetically used to degrade dyes through ultrasonic dispersion and ultraviolet radiation. The material improves dispersion and adsorption properties through chemical bonding and porous structure design.

Benefits of technology

The antibacterial properties, adsorption properties and degradation properties of graphene-based composite materials used to degrade dyes have been significantly improved, and the problems of nano-Fe3O4 agglomeration and microbial invasion have been solved, and the overall performance of the material has been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of nano materials and environmental science, and particularly discloses a magnetic graphene-based composite material for degrading dye and a preparation method thereof, the magnetic graphene-based composite material is prepared from the following raw materials in parts by weight: 36-44 parts of functionalized graphene oxide, 6-8 parts of sulfhydrylation core-shell particles, 0.02-0.06 part of a photoinitiator and 320-360 parts of deionized water; the antibacterial activity of the functionalized graphene oxide is embodied in an aniline structure, a chitosan structure and a graphene oxide structure, the adsorbability of the functionalized graphene oxide is embodied in improvement of the dispersing performance of the modified graphene oxide, and the antibacterial activity of the sulfhydrylated core-shell particles is embodied in a nano magnetic ferroferric oxide structure, a titanium dioxide structure and a pyrimidine ring structure. The adsorbability and the degradability of the sulfhydrylation core-shell particle are reflected in a structure obtained by bonding the sulfhydrylation core-shell particle and the functionalized graphene oxide and a porous core-shell structure, and through the synergistic effect of the structures, the antibacterial activity, the adsorbability and the degradability of the material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of nanomaterials and environmental science and technology, and more specifically, to a magnetic graphene-based composite material for degrading dyes and a preparation method thereof. Background Art

[0002] While the textile printing and dyeing industry is developing rapidly, it is also accompanied by a large number of environmental problems, and water pollution is one of the most urgent problems to be solved. In order to ensure the sustainable development of the printing and dyeing industry, reduce the threat to water sources, and protect human health, it is necessary to solve the water pollution problem caused by the printing and dyeing industry. Therefore, it is of great significance to seek a simple and feasible new method for treating printing and dyeing wastewater.

[0003] The methods for dye wastewater mainly include adsorption, biotechnology, catalytic process, membrane technology, ionizing radiation technology and magnetic field assisted process, etc. Among them, physical adsorption based on various adsorption materials to treat pollutants in wastewater has the advantages of easy operation, fast speed, high efficiency and strong adaptability. In addition, this type of adsorption material is usually not soluble in water, and only adsorbs pollutants on the surface of the material without further chemical reaction, so usually no new pollutants are generated in the water body and are easy to separate. Nano Fe 3 O 4 It is a new type of magnetic adsorption material, which has attracted wide attention due to its high adsorption capacity and selectivity and easy separation and recovery. The existing technology has successfully combined it with graphene oxide with a large specific surface area to prepare a graphene-based composite material with magnetic properties. However, nano-Fe 3 O 4 It is easy to agglomerate, resulting in uneven dispersion on the surface of graphene oxide. At the same time, in the sewage treatment process, there are microorganisms that are easy to occupy the active adsorption sites. These will cause the adsorption and degradation properties of the prepared graphene-based composite materials to decrease.

[0004] Based on the above statements, the present application provides a magnetic graphene-based composite material for degrading dyes and a preparation method thereof. Summary of the invention

[0005] In order to solve the problem of nano-Fe 3 O 4 It is easy to agglomerate, resulting in uneven dispersion on the surface of graphene oxide. At the same time, in the sewage treatment process, there is a problem that microorganisms are easy to occupy the active adsorption sites, resulting in the adsorption and degradation properties of the prepared graphene-based composite material being reduced. The present application provides a magnetic graphene-based composite material for degrading dyes and a preparation method thereof.

[0006] A magnetic graphene-based composite material for degrading dyes, comprising the following raw materials in parts by weight: 36-44 parts of functionalized graphene oxide, 6-8 parts of thiol core-shell particles, 0.02-0.06 parts of photoinitiator and 320-360 parts of deionized water; The preparation method of the magnetic graphene-based composite material for degrading dyes comprises the following steps: Functionalized graphene oxide is ultrasonically dispersed in deionized water, heated to 60-70°C, and then thiol core-shell particles and a photoinitiator are added, stirred evenly, irradiated with ultraviolet light for 10-20 minutes, rotary evaporated, washed, and dried to obtain a magnetic graphene-based composite material for degrading dyes.

[0007] Preferably, the photoinitiator is sodium 2-hydroxy-3-(4-benzoylphenoxy)propanesulfonate.

[0008] Preferably, the peak wavelength of the irradiation is 365nm and the intensity is 80mw / cm 2 .

[0009] Preferably, the functionalized graphene oxide is prepared by the following steps: Step A1, add succinic acid to anhydrous ethanol, heat to 40-46°C, stir evenly, then add a mixed solution a of N, N'-dicyclohexylcarbodiimide, 4-dimethylaminopyridine, aniline and anhydrous ethanol, heat to reflux, stir and react for 4-6 hours, centrifuge after the reaction, wash and dry the precipitate to obtain an unsaturated monomer, wherein the mass ratio of succinic acid, anhydrous ethanol and mixed solution b is 2-4:46-54:22-28, in the mixed solution a, N, N'-dicyclohexylcarbodiimide , 4-dimethylaminopyridine, aniline and anhydrous ethanol in a mass ratio of 4-7:3-5:1.5-3.1:32. In the above reaction process, N, N'-dicyclohexylcarbodiimide is used as a dehydrating agent and 4-dimethylaminopyridine is used as an acylating agent to make the carboxyl group on the butenedioic acid and the amino group on the aniline undergo an amidation reaction to obtain an unsaturated monomer. During the reaction, the amount of the butenedioic acid is controlled to be slightly higher than the amount of the aniline, so that after the reaction is completed, there are still remaining carboxyl groups that can participate in the subsequent reaction process; Step A2, mixing graphene oxide and deionized water, and ultrasonically dispersing to obtain a graphene oxide suspension; at room temperature, adjusting the pH value to 8-9, dripping a mixed solution b of an unsaturated monomer and anhydrous DMF, and controlling the dripping to be completed within 15 minutes, heating to 75-85° C. under a nitrogen atmosphere, maintaining a constant speed, stirring and reacting for 10-20 minutes, filtering, washing, and drying to obtain modified graphene oxide, wherein the mass ratio of graphene oxide to deionized water is 1:100, the mass ratio of graphene oxide suspension to mixed solution b is 20-30:14-16, and the mass ratio of unsaturated monomer to anhydrous DMF in mixed solution b is 3-5:20. In the above reaction process, the amino group on the unsaturated monomer can undergo an amidation reaction with the carboxyl group on the surface of graphene oxide to be grafted on the surface of graphene oxide, thereby reducing the agglomeration of graphene oxide, improving the dispersion performance of graphene oxide, and improving the adsorption performance of graphene oxide; Step A3, chitosan, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide are added to an acetic acid aqueous solution, stirred evenly, and then the modified graphene oxide aqueous solution is added, the temperature is raised to 54-66°C, stirred for reaction for 1-2h, cooled to room temperature, the pH value is adjusted to neutral, filtered under reduced pressure, washed, and dried to obtain functionalized graphene oxide, wherein chitosan, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, The mass ratio of N-hydroxysuccinimide, acetic acid aqueous solution and modified graphene oxide aqueous solution is 0.6:3-4:2.6-3.0:25-35:46-52. The modified graphene oxide aqueous solution is obtained by ultrasonic dispersion of modified graphene oxide and deionized water in a mass ratio of 1:10. The mass fraction of acetic acid aqueous solution is 0.6-1%. In the above process, the active amino group on chitosan undergoes amidation reaction with the carboxyl group on the modified graphene oxide to obtain functionalized graphene oxide.

[0010] Preferably, the thiol core-shell particles are prepared by the following steps: Step B1, ultrasonically disperse nano-magnetic ferroferric oxide in anhydrous ethanol, drip tetrabutyl titanate, hexadecyltrimethylammonium bromide, a mixed solution c of anhydrous ethanol and deionized water, and control the dripping to be completed within 10 minutes. After the dripping is completed, adjust the pH to 2-3, heat to 44-52°C, keep stirring for 18-22 minutes, then heat to reflux, stir and react for 6-8 hours to obtain modified core-shell particles, wherein the mass ratio of nano-magnetic ferroferric oxide, anhydrous ethanol and mixed solution c is 2.4-3.2:50-60 : 20-26, in the mixed solution c, the mass ratio of tetrabutyl titanate, hexadecyltrimethylammonium bromide, anhydrous ethanol and deionized water is 12-14:1:8-10:3-5, in the above reaction process, the stability of ferroferric oxide is poor, the above step uses anhydrous ethanol as a solvent and hexadecyltrimethylammonium bromide as a porogen, and utilizes a sol-gel method to coat porous titanium dioxide on the surface of ferroferric oxide, which not only improves its antioxidant property and stability, stabilizes its magnetic properties, but also improves its adsorption performance and degradation performance; Step B2, ultrasonically mixing the modified core-shell particles, deionized water, anhydrous ethanol and KH-560 for 20-30 minutes, stirring at room temperature for 6-8 hours, centrifuging, washing and drying the precipitate to obtain epoxy core-shell particles, ultrasonically dispersing the epoxy core-shell particles and anhydrous DMF, dripping a mixture of tetrabutylammonium bromide, 2-mercaptonicotinic acid and anhydrous DMF, heating to 105-115° C., stirring for 2-3 hours, centrifuging after the reaction, washing and drying the precipitate to obtain thiolated core-shell particles, wherein the mass ratio of the modified core-shell particles, deionized water, anhydrous ethanol and KH-560 is 3-5 : 12:30-34:0.4-0.6, the mass ratio of epoxy core-shell particles, anhydrous DMF and mixed liquid d is 2-4:44-50:14, and in the mixed liquid d, the mass ratio of tetrabutylammonium bromide, 2-mercaptonicotinic acid and anhydrous DMF is 0.2:1.2-1.6:12. In the above reaction process, the core-shell particles are first treated with KH-560, and then under the action of tetrabutylammonium bromide, the carboxyl group of 2-mercaptonicotinic acid undergoes a ring-opening esterification reaction with the epoxy group to obtain thiolated core-shell particles. In the above reaction, a pyridine ring with antibacterial properties and a chemically active thiol group are introduced to pave the way for subsequent reactions.

[0011] In summary, the present application has the following beneficial effects: the present invention adds functionalized graphene oxide and thiolated core-shell particles in the process of preparing a magnetic graphene-based composite material for degrading dyes, the functionalized graphene oxide is prepared by chemically bonding chitosan and modified graphene oxide, the modified graphene oxide is firstly chemically bonded by butenedioic acid and aniline, and then chemically bonded with graphene oxide, the prepared modified graphene oxide has antibacterial properties on the one hand, and adsorption properties on the other hand, the antibacterial properties are reflected in the aniline structure, the chitosan structure and the graphene oxide structure, and the adsorption properties are reflected in the π-π interaction between the modified graphene oxide structure and the chitosan structure, so that the modified graphene oxide has good antibacterial properties. The graphene structure is adsorbed on the surface of the chitosan structure, which improves the dispersibility of graphene oxide and the adsorption performance of the graphene-based composite material. The thiolated core-shell particles are prepared by chemical combination of phenyl chitosan and pyrimidine derivatives containing thiol groups, which play an antibacterial role on the one hand, and an adsorption and degradation performance on the other hand. The antibacterial performance is embodied in the nano-magnetic ferroferric oxide structure, titanium dioxide structure and pyrimidine ring structure, and the adsorption and degradation properties are embodied in the three-dimensional network structure and porous core-shell structure obtained by chemical bonding of the thiol groups of the thiol-containing core-shell particles and functionalized graphene oxide. In addition, the porous core-shell structure exists, which reduces the agglomeration phenomenon and further improves its adsorption and degradation properties. In summary, the present invention improves the antibacterial performance, adsorption and degradation properties of the magnetic graphene-based composite material used for degrading dyes through the combined action of the above-mentioned structures. DETAILED DESCRIPTION

[0012] In order to make the implementation methods of the present application easier to understand, the present application will be described in detail below in conjunction with specific examples. These examples are only for illustration and are not limited to the scope of application of the present application.

[0013] Preparation Examples 1-3 and Comparative Preparation Examples 1-2 provide a functionalized graphene oxide.

[0014] Preparation Example 1 This preparation example provides a functionalized graphene oxide, which is prepared by the following steps: Step A1, adding butenedioic acid to anhydrous ethanol, heating to 40°C, stirring at a speed of 450rpm for 12min until uniform, then adding a mixed solution a of N,N'-dicyclohexylcarbodiimide, 4-dimethylaminopyridine, aniline and anhydrous ethanol, heating to reflux, maintaining the speed unchanged, and continuing to stir and react for 4h. After the reaction is completed, centrifugation is performed, and the precipitate is washed with anhydrous ethanol and deionized water three times in sequence, and dried at 50°C to constant weight to obtain an unsaturated monomer, wherein the mass ratio of butenedioic acid, anhydrous ethanol and mixed solution a is 2:46:22, and the mass ratio of N,N'-dicyclohexylcarbodiimide, 4-dimethylaminopyridine, aniline and anhydrous ethanol in the mixed solution a is 4:3:1.5:32; Step A2, mixing graphene oxide and deionized water, ultrasonically treating for 16 minutes at an ultrasonic frequency of 25kHz and an ultrasonic power of 400w to obtain a graphene oxide suspension; at room temperature, adjusting the pH value to 8 with a 0.6M sodium hydroxide aqueous solution, dripping a mixed solution b of an unsaturated monomer and anhydrous DMF, and controlling the dripping to be completed within 15 minutes, after the dripping is completed, heating to 75°C under a nitrogen atmosphere, maintaining the speed unchanged, stirring the reaction for 10 minutes, filtering, washing with anhydrous ethanol and deionized water for 3 times in sequence, and drying at 55°C to constant weight to obtain modified graphene oxide, wherein the mass ratio of graphene oxide to deionized water is 1:100, the mass ratio of graphene oxide suspension to mixed solution b is 20:14, and the mass ratio of unsaturated monomer to anhydrous DMF in mixed solution b is 3:20; Step A3, chitosan, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide are added to an acetic acid aqueous solution, stirred at a speed of 650 rpm for 18 minutes until uniform, then the modified graphene oxide aqueous solution is added, the temperature is raised to 54°C, the speed is maintained unchanged, the stirring reaction is continued for 1 hour, and the mixture is cooled to room temperature. The pH value is adjusted to neutral with a 0.6M sodium hydroxide aqueous solution, the mixture is filtered under reduced pressure, washed with deionized water for 3 times, and dried at 55°C to constant weight to obtain functionalized graphene oxide, wherein the mass ratio of chitosan, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, N-hydroxysuccinimide, acetic acid aqueous solution and modified graphene oxide aqueous solution is 0.6:3:2.6:25:46, the modified graphene oxide aqueous solution is obtained by ultrasonically dispersing the modified graphene oxide and deionized water at a mass ratio of 1:10, and the mass fraction of the acetic acid aqueous solution is 0.6%.

[0015] Preparation Example 2 This preparation example provides a functionalized graphene oxide, which is prepared by the following steps: Step A1, adding butenedioic acid to anhydrous ethanol, heating to 43°C, stirring at a speed of 500 rpm for 8 minutes until uniform, then adding a mixed solution a of N, N'-dicyclohexylcarbodiimide, 4-dimethylaminopyridine, aniline and anhydrous ethanol, heating to reflux, maintaining the speed unchanged, stirring and reacting for 5 hours, centrifuging after the reaction, washing the precipitate with anhydrous ethanol and deionized water for 4 times in sequence, and drying at 55°C to constant weight to obtain an unsaturated monomer, wherein the mass ratio of butenedioic acid, anhydrous ethanol and mixed solution a is 3:50:25, and the mass ratio of N, N'-dicyclohexylcarbodiimide, 4-dimethylaminopyridine, aniline and anhydrous ethanol in the mixed solution a is 5.5:4:2.3:32; Step A2, mixing graphene oxide and deionized water, ultrasonically treating for 20 minutes at an ultrasonic frequency of 30kHz and an ultrasonic power of 450w to obtain a graphene oxide suspension; at room temperature, adjusting the pH value to 8.5 with a 0.8M sodium hydroxide aqueous solution, dripping a mixed solution b of an unsaturated monomer and anhydrous DMF, and controlling the dripping to be completed within 15 minutes, after the dripping is completed, heating to 80°C under a nitrogen atmosphere, maintaining the speed unchanged, stirring and reacting for 15 minutes, filtering, washing with anhydrous ethanol and deionized water 4 times in sequence, and drying at 60°C to constant weight to obtain modified graphene oxide, wherein the mass ratio of graphene oxide to deionized water is 1:100, the mass ratio of graphene oxide suspension to mixed solution b is 25:15, and the mass ratio of unsaturated monomer to anhydrous DMF in mixed solution b is 4:20; Step A3, chitosan, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide are added to an acetic acid aqueous solution, stirred at a speed of 700 rpm for 22 minutes until uniform, then the modified graphene oxide aqueous solution is added, the temperature is raised to 60°C, the speed is maintained unchanged, the stirring reaction is continued for 1.5 hours, and the mixture is cooled to room temperature. The pH value is adjusted to neutral with a 0.8M sodium hydroxide aqueous solution, the mixture is filtered under reduced pressure, washed with deionized water for 4 times, and dried at 60°C to constant weight to obtain functionalized graphene oxide, wherein the mass ratio of chitosan, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, N-hydroxysuccinimide, acetic acid aqueous solution and modified graphene oxide aqueous solution is 0.6:3.5:2.8:30:49, the modified graphene oxide aqueous solution is obtained by ultrasonically dispersing the modified graphene oxide and deionized water at a mass ratio of 1:10, and the mass fraction of the acetic acid aqueous solution is 0.8%.

[0016] Preparation Example 3 This preparation example provides a functionalized graphene oxide, which is prepared by the following steps: Step A1, adding butenedioic acid to anhydrous ethanol, heating to 46°C, stirring at a speed of 550 rpm for 4 minutes until uniform, then adding a mixed solution a of N, N'-dicyclohexylcarbodiimide, 4-dimethylaminopyridine, aniline and anhydrous ethanol, heating to reflux, stirring and reacting for 6 hours, centrifuging after the reaction, washing the precipitate with anhydrous ethanol and deionized water for 5 times in sequence, and drying at 60°C to constant weight to obtain an unsaturated monomer, wherein the mass ratio of butenedioic acid, anhydrous ethanol and mixed solution a is 4:54:28, and the mass ratio of N, N'-dicyclohexylcarbodiimide, 4-dimethylaminopyridine, aniline and anhydrous ethanol in the mixed solution a is 7:5:3.1:32; Step A2, mixing graphene oxide and deionized water, ultrasonically treating at an ultrasonic frequency of 35kHz and an ultrasonic power of 500w for 24min to obtain a graphene oxide suspension; at room temperature, adjusting the pH value to 9 with a 1.0M sodium hydroxide aqueous solution, dripping a mixed solution b of an unsaturated monomer and anhydrous DMF, and controlling the dripping to be completed within 15min, after the dripping is completed, heating to 85°C under a nitrogen atmosphere, maintaining the speed unchanged, stirring and reacting for 20min, filtering, washing with anhydrous ethanol and deionized water for 5 times in sequence, and drying at 60°C to constant weight to obtain modified graphene oxide, wherein the mass ratio of graphene oxide to deionized water is 1:100, the mass ratio of graphene oxide suspension to mixed solution b is 30:16, and the mass ratio of unsaturated monomer to anhydrous DMF in mixed solution b is 5:20; Step A3, chitosan, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide are added to an acetic acid aqueous solution, stirred at a speed of 750 rpm for 26 minutes until uniform, then the modified graphene oxide aqueous solution is added, the temperature is raised to 66°C, the speed is maintained unchanged, the stirring reaction is continued for 2 hours, and the mixture is cooled to room temperature. The pH value is adjusted to neutral with a 1.0M sodium hydroxide aqueous solution, the mixture is filtered under reduced pressure, washed with deionized water for 5 times, and dried at 65°C to constant weight to obtain functionalized graphene oxide, wherein the mass ratio of chitosan, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, N-hydroxysuccinimide, acetic acid aqueous solution and modified graphene oxide aqueous solution is 0.6:4:3.0:35:52, the modified graphene oxide aqueous solution is obtained by ultrasonically dispersing the modified graphene oxide and deionized water at a mass ratio of 1:10, and the mass fraction of the acetic acid aqueous solution is 1%.

[0017] Comparative Preparation Example 1 This comparative preparation example provides a functionalized graphene oxide, which is prepared by the following steps: Step A1, adding succinic acid to anhydrous ethanol, heating to 40°C, stirring at a speed of 450 rpm for 12 min until uniform, then adding a mixed solution a of N, N'-dicyclohexylcarbodiimide, 4-dimethylaminopyridine, aniline and anhydrous ethanol, heating to reflux, maintaining the speed unchanged, and continuing to stir and react for 4 hours. After the reaction is completed, centrifugation is performed, and the precipitate is washed with anhydrous ethanol and deionized water three times in sequence, and dried at 50°C to constant weight to obtain an unsaturated monomer, wherein the mass ratio of succinic acid, anhydrous ethanol and mixed solution a is 2:46:22, and the mass ratio of N, N'-dicyclohexylcarbodiimide, 4-dimethylaminopyridine, aniline and anhydrous ethanol in the mixed solution a is 4:3:1.5:32; Step A2, mixing graphene oxide and deionized water, ultrasonically treating for 16 minutes at an ultrasonic frequency of 25kHz and an ultrasonic power of 400w to obtain a graphene oxide suspension; at room temperature, adjusting the pH value to 8 with a 0.6M sodium hydroxide aqueous solution, dripping a mixed solution b of an unsaturated monomer and anhydrous DMF, and controlling the dripping to be completed within 15 minutes, after the dripping is completed, heating to 75°C under a nitrogen atmosphere, maintaining the speed unchanged, stirring the reaction for 10 minutes, filtering, washing with anhydrous ethanol and deionized water for 3 times in sequence, and drying at 55°C to constant weight to obtain modified graphene oxide, wherein the mass ratio of graphene oxide to deionized water is 1:100, the mass ratio of graphene oxide suspension to mixed solution b is 20:14, and the mass ratio of unsaturated monomer to anhydrous DMF in mixed solution b is 3:20; Step A3, chitosan, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide are added to an acetic acid aqueous solution, stirred at a speed of 650 rpm for 18 minutes until uniform, then the modified graphene oxide aqueous solution is added, the temperature is raised to 54°C, the speed is maintained unchanged, the stirring reaction is continued for 1 hour, and the mixture is cooled to room temperature. The pH value is adjusted to neutral with a 0.6M sodium hydroxide aqueous solution, the mixture is filtered under reduced pressure, washed with deionized water for 3 times, and dried at 55°C to constant weight to obtain functionalized graphene oxide, wherein the mass ratio of chitosan, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, N-hydroxysuccinimide, acetic acid aqueous solution and modified graphene oxide aqueous solution is 0.6:3:2.6:25:46, the modified graphene oxide aqueous solution is obtained by ultrasonically dispersing the modified graphene oxide and deionized water at a mass ratio of 1:10, and the mass fraction of the acetic acid aqueous solution is 0.6%.

[0018] Comparative Preparation Example 2 This comparative preparation example provides a functionalized graphene oxide, which is prepared by the following steps: Step A1, add butenedioic acid to anhydrous ethanol, heat to 40°C, stir at a speed of 450rpm for 12min until uniform, then add a mixed solution a of N,N'-dicyclohexylcarbodiimide, 4-dimethylaminopyridine, cyclopentylamine and anhydrous ethanol, heat to reflux, maintain the speed unchanged, continue stirring to react for 4h, centrifuge after the reaction, wash the precipitate with anhydrous ethanol and deionized water three times in sequence, and dry at 50°C to constant weight to obtain an unsaturated monomer, wherein the mass ratio of butenedioic acid, anhydrous ethanol and mixed solution a is 2:46:22, and the mass ratio of N,N'-dicyclohexylcarbodiimide, 4-dimethylaminopyridine, cyclopentylamine and anhydrous ethanol in the mixed solution a is 4:3:1.5:32; Step A2, mixing graphene oxide and deionized water, ultrasonically treating for 16 minutes at an ultrasonic frequency of 25kHz and an ultrasonic power of 400w to obtain a graphene oxide suspension; at room temperature, adjusting the pH value to 8 with a 0.6M sodium hydroxide aqueous solution, dripping a mixed solution b of an unsaturated monomer and anhydrous DMF, and controlling the dripping to be completed within 15 minutes, after the dripping is completed, heating to 75°C under a nitrogen atmosphere, maintaining the speed unchanged, stirring the reaction for 10 minutes, filtering, washing with anhydrous ethanol and deionized water for 3 times in sequence, and drying at 55°C to constant weight to obtain modified graphene oxide, wherein the mass ratio of graphene oxide to deionized water is 1:100, the mass ratio of graphene oxide suspension to mixed solution b is 20:14, and the mass ratio of unsaturated monomer to anhydrous DMF in mixed solution b is 3:20; Step A3, chitosan, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide are added to an acetic acid aqueous solution, stirred at a speed of 650 rpm for 18 minutes until uniform, then the modified graphene oxide aqueous solution is added, the temperature is raised to 54°C, the speed is maintained unchanged, the stirring reaction is continued for 1 hour, and the mixture is cooled to room temperature. The pH value is adjusted to neutral with a 0.6M sodium hydroxide aqueous solution, the mixture is filtered under reduced pressure, washed with deionized water for 3 times, and dried at 55°C to constant weight to obtain functionalized graphene oxide, wherein the mass ratio of chitosan, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, N-hydroxysuccinimide, acetic acid aqueous solution and modified graphene oxide aqueous solution is 0.6:3:2.6:25:46, the modified graphene oxide aqueous solution is obtained by ultrasonically dispersing the modified graphene oxide and deionized water at a mass ratio of 1:10, and the mass fraction of the acetic acid aqueous solution is 0.6%.

[0019] Preparation Examples 4-6 and Comparative Preparation Examples 3-4 provide a thiol-containing core-shell particle.

[0020] Preparation Example 4 This preparation example provides a thiolated core-shell particle, which is prepared by the following steps: Step B1, ultrasonically disperse nano-magnetic ferroferric oxide in anhydrous ethanol, control the ultrasonic frequency to 25kHz, the ultrasonic power to 400w, the ultrasonic time to 8min, and drop a mixed solution c of tetrabutyl titanate, hexadecyltrimethylammonium bromide, anhydrous ethanol and deionized water at a rotation speed of 600pm, and control the dripping to be completed within 10min. After the dripping is completed, adjust the pH to 2 with 0.8M hydrochloric acid water, heat to 44°C, keep stirring for 18min, then heat to reflux, stir and react for 6h to obtain modified core-shell particles, wherein the mass ratio of nano-magnetic ferroferric oxide, anhydrous ethanol and mixed solution c is 2.4:50:20, and the mass ratio of tetrabutyl titanate, hexadecyltrimethylammonium bromide, anhydrous ethanol and deionized water in the mixed solution c is 12:1:8:3; Step B2, the modified core-shell particles, deionized water, anhydrous ethanol and KH-560 were ultrasonically mixed at an ultrasonic frequency of 25kHz and an ultrasonic power of 400w for 20min, stirred at a speed of 650rpm at room temperature for 6h, centrifuged, and the precipitate was washed 3 times with a 20% ethanol aqueous solution by mass fraction, and dried at 55°C to constant weight to obtain epoxy core-shell particles. The epoxy core-shell particles and anhydrous DMF were ultrasonically dispersed, the ultrasonic frequency was controlled to be 25kHz, the ultrasonic power was 400w, and the ultrasonic time was 16min. Tetrabutylammonium bromide and 2-mercapto-nicotinic acid were added dropwise. After the addition of the mixed solution d of acid and anhydrous DMF is completed, the temperature is raised to 105°C and stirred for 2 hours. After the reaction is completed, the mixture is centrifuged, and the precipitate is washed three times with anhydrous ethanol and deionized water, and dried at 50°C to constant weight to obtain thiolated core-shell particles, wherein the mass ratio of modified core-shell particles, deionized water, anhydrous ethanol and KH-560 is 3:12:30:0.4, the mass ratio of epoxy core-shell particles, anhydrous DMF and the mixed solution d is 2:44:14, and the mass ratio of tetrabutylammonium bromide, 2-mercaptonicotinic acid and anhydrous DMF in the mixed solution d is 0.2:1.2:12.

[0021] Preparation Example 5 This preparation example provides a thiolated core-shell particle, which is prepared by the following steps: Step B1, ultrasonically dispersing nano-magnetic ferroferric oxide into anhydrous ethanol, controlling the ultrasonic frequency to 30kHz, the ultrasonic power to 450w, the ultrasonic time to 10min, and dropping a mixed solution c of tetrabutyl titanate, hexadecyltrimethylammonium bromide, anhydrous ethanol and deionized water at a speed of 650rpm while stirring, and controlling the dropping to be completed within 10min. After the dropping is completed, adjusting the pH to 2.5 with 1.0M hydrochloric acid water, heating to 48°C, keeping warm and stirring for 20min, then heating to reflux, stirring and reacting for 7h to obtain modified core-shell particles, wherein the mass ratio of nano-magnetic ferroferric oxide, anhydrous ethanol and mixed solution c is 2.8:55:23, and the mass ratio of tetrabutyl titanate, hexadecyltrimethylammonium bromide, anhydrous ethanol and deionized water in the mixed solution c is 13:1:9:4; Step B2, the modified core-shell particles, deionized water, anhydrous ethanol and KH-560 were ultrasonically mixed at an ultrasonic frequency of 35kHz and an ultrasonic power of 500w for 25min, stirred at a speed of 600rpm and reacted at room temperature for 7h, centrifuged, and the precipitate was washed 4 times with a mass fraction of 25% ethanol aqueous solution, and dried at 60°C to constant weight to obtain epoxy core-shell particles, and the epoxy core-shell particles and anhydrous DMF were ultrasonically dispersed, the ultrasonic frequency was controlled to 30kHz, the ultrasonic power was 450w, and the ultrasonic time was 18min, and tetrabutylammonium bromide and 2-mercaptonicotinic acid were added dropwise and anhydrous DMF, after the addition is completed, the temperature is raised to 110°C and stirred for 2.5 hours. After the reaction is completed, the precipitate is centrifuged, and the precipitate is washed 4 times with anhydrous ethanol and deionized water, and dried at 55°C to constant weight to obtain thiolated core-shell particles, wherein the mass ratio of modified core-shell particles, deionized water, anhydrous ethanol and KH-560 is 4:12:32:0.5, the mass ratio of epoxy core-shell particles, anhydrous DMF and mixed solution d is 3:47:14, and in the mixed solution d, the mass ratio of tetrabutylammonium bromide, 2-mercaptonicotinic acid and anhydrous DMF is 0.2:1.4:12.

[0022] Preparation Example 6 This preparation example provides a thiolated core-shell particle, which is prepared by the following steps: Step B1, ultrasonically dispersing nano-magnetic ferroferric oxide into anhydrous ethanol, controlling the ultrasonic frequency to 35kHz, the ultrasonic power to 500w, the ultrasonic time to 12min, adding tetrabutyl titanate, hexadecyltrimethylammonium bromide, a mixed solution c of anhydrous ethanol and deionized water dropwise while stirring at a speed of 700rpm, and controlling the dripping to be completed within 10min. After the dripping, adjusting the pH to 3 with 1.2M hydrochloric acid water, heating to 52°C, keeping warm and stirring for 22min, then heating to reflux, stirring and reacting for 8h, to obtain modified core-shell particles, wherein the mass ratio of nano-magnetic ferroferric oxide, anhydrous ethanol and the mixed solution c is 3:60:26, and the mass ratio of tetrabutyl titanate, hexadecyltrimethylammonium bromide, anhydrous ethanol and deionized water in the mixed solution c is 14:1:10:3; Step B2, the modified core-shell particles, deionized water, anhydrous ethanol and KH-560 were ultrasonically mixed for 30 minutes at an ultrasonic frequency of 30kHz and an ultrasonic power of 450w, and the reaction was stirred at room temperature for 8 hours at a speed of 650rpm, and the precipitate was washed 5 times with a mass fraction of 30% ethanol aqueous solution, and dried at 65°C to constant weight to obtain epoxy core-shell particles. The epoxy core-shell particles and anhydrous DMF were ultrasonically dispersed, and the ultrasonic frequency was controlled to be 35kHz, the ultrasonic power was 500w, and the ultrasonic time was 20min. Tetrabutylammonium bromide and 2-mercapto-nicotinic acid were added dropwise. After the addition of the mixed solution d of acid and anhydrous DMF is completed, the temperature is raised to 115°C and stirred for 3 hours. After the reaction is completed, the mixture is centrifuged, and the precipitate is washed 5 times with anhydrous ethanol and deionized water, and dried at 60°C to constant weight to obtain thiolated core-shell particles, wherein the mass ratio of modified core-shell particles, deionized water, anhydrous ethanol and KH-560 is 5:12:34:0.6, the mass ratio of epoxy core-shell particles, anhydrous DMF and the mixed solution d is 4:50:14, and the mass ratio of tetrabutylammonium bromide, 2-mercaptonicotinic acid and anhydrous DMF in the mixed solution d is 0.2:1.6:12.

[0023] Comparative Preparation Example 3 This comparative preparation example provides a thiolated core-shell particle, which is prepared by the following steps: Step B1, ultrasonically disperse nano-magnetic ferroferric oxide in anhydrous ethanol, control the ultrasonic frequency to 25kHz, the ultrasonic power to 400w, the ultrasonic time to 8min, and drop a mixed solution c of tetrabutyl titanate, methylammonium bromide, anhydrous ethanol and deionized water at a rotation speed of 600pm, and control the dripping to be completed within 10min. After the dripping is completed, adjust the pH to 2 with 0.8M hydrochloric acid water, heat to 44°C, keep stirring for 18min, then heat to reflux, stir and react for 6h to obtain modified core-shell particles, wherein the mass ratio of nano-magnetic ferroferric oxide, anhydrous ethanol and mixed solution c is 2.4:50:20, and the mass ratio of tetrabutyl titanate, methylammonium bromide, anhydrous ethanol and deionized water in the mixed solution c is 12:1:8:3; Step B2, the modified core-shell particles, deionized water, anhydrous ethanol and KH-560 were ultrasonically mixed at an ultrasonic frequency of 25kHz and an ultrasonic power of 400w for 20min, stirred at a speed of 650rpm at room temperature for 6h, centrifuged, and the precipitate was washed 3 times with a 20% ethanol aqueous solution by mass fraction, and dried at 55°C to constant weight to obtain epoxy core-shell particles. The epoxy core-shell particles and anhydrous DMF were ultrasonically dispersed, the ultrasonic frequency was controlled to be 25kHz, the ultrasonic power was 400w, and the ultrasonic time was 16min. Tetrabutylammonium bromide and 2-mercapto-nicotinic acid were added dropwise. After the addition of the mixed solution d of acid and anhydrous DMF is completed, the temperature is raised to 105°C and stirred for 2 hours. After the reaction is completed, the mixture is centrifuged, and the precipitate is washed three times with anhydrous ethanol and deionized water, and dried at 50°C to constant weight to obtain thiolated core-shell particles, wherein the mass ratio of modified core-shell particles, deionized water, anhydrous ethanol and KH-560 is 3:12:30:0.4, the mass ratio of epoxy core-shell particles, anhydrous DMF and the mixed solution d is 2:44:14, and the mass ratio of tetrabutylammonium bromide, 2-mercaptonicotinic acid and anhydrous DMF in the mixed solution d is 0.2:1.2:12.

[0024] Comparative Preparation Example 4 This comparative preparation example provides a thiolated core-shell particle, which is prepared by the following steps: Step B1, ultrasonically disperse nano-magnetic ferroferric oxide in anhydrous ethanol, control the ultrasonic frequency to 25kHz, the ultrasonic power to 400w, the ultrasonic time to 8min, and drop a mixed solution c of tetrabutyl titanate, hexadecyltrimethylammonium bromide, anhydrous ethanol and deionized water at a rotation speed of 600pm, and control the dripping to be completed within 10min. After the dripping is completed, adjust the pH to 2 with 0.8M hydrochloric acid water, heat to 44°C, keep stirring for 18min, then heat to reflux, stir and react for 6h to obtain modified core-shell particles, wherein the mass ratio of nano-magnetic ferroferric oxide, anhydrous ethanol and mixed solution c is 2.4:50:20, and the mass ratio of tetrabutyl titanate, hexadecyltrimethylammonium bromide, anhydrous ethanol and deionized water in the mixed solution c is 12:1:8:3; Step B2, the modified core-shell particles, deionized water, anhydrous ethanol and KH-560 were ultrasonically mixed at an ultrasonic frequency of 25kHz and an ultrasonic power of 400w for 20min, stirred at a speed of 650rpm at room temperature for 6h, centrifuged, and the precipitate was washed 3 times with a mass fraction of 20% ethanol aqueous solution, and dried at 55°C to constant weight to obtain epoxy core-shell particles. The epoxy core-shell particles and anhydrous DMF were ultrasonically dispersed, the ultrasonic frequency was controlled to be 25kHz, the ultrasonic power was 400w, and the ultrasonic time was 16min. Tetrabutylammonium bromide and 3-mercaptoethanol were added dropwise. After the addition of propionic acid and anhydrous DMF mixed solution d is completed, the temperature is raised to 105°C and stirred for 2 hours. After the reaction is completed, the mixture is centrifuged, and the precipitate is washed three times with anhydrous ethanol and deionized water, and dried at 50°C to constant weight to obtain thiolated core-shell particles, wherein the mass ratio of modified core-shell particles, deionized water, anhydrous ethanol and KH-560 is 3:12:30:0.4, the mass ratio of epoxy core-shell particles, anhydrous DMF and mixed solution d is 2:44:14, and in the mixed solution d, the mass ratio of tetrabutylammonium bromide, 3-mercaptopropionic acid and anhydrous DMF is 0.2:1.2:12.

[0025] Examples 1-3 and Comparative Examples 1-4 provide a magnetic graphene-based composite material for degrading dyes.

[0026] Example 1 This embodiment provides a magnetic graphene-based composite material for degrading dyes, comprising the following raw materials in parts by weight: 36 parts of functionalized graphene oxide prepared in Preparation Example 1, 6 parts of thiolated core-shell particles prepared in Preparation Example 4, 0.02 parts of sodium 2-hydroxy-3-(4-benzoylphenoxy)propanesulfonate, and 320 parts of deionized water; The preparation method of the magnetic graphene-based composite material for degrading dyes comprises the following steps: Functionalized graphene oxide was ultrasonically dispersed in deionized water, the ultrasonic frequency was controlled to be 35kHz, the ultrasonic power was 500w, the ultrasonic time was 16min, and the temperature was raised to 60°C while stirring at a speed of 550rpm. Then, thiolated core-shell particles and sodium 2-hydroxy-3-(4-benzoylphenoxy)propanesulfonate were added, the speed was maintained unchanged, and stirring was continued for 12min until uniform, and then placed at a wavelength peak of 365nm and an intensity of 80mw / cm 2 The mixture was placed under ultraviolet light for 10 min, the rotary evaporation temperature was controlled to be 50°C, the deionized water was removed by rotary evaporation, the mixture was washed with deionized water for 3 times, and the mixture was dried at 60°C to constant weight to obtain a magnetic graphene-based composite material for dye degradation.

[0027] Example 2 This embodiment provides a magnetic graphene-based composite material for degrading dyes, comprising the following raw materials in parts by weight: 40 parts of functionalized graphene oxide prepared in Preparation Example 2, 7 parts of thiolated core-shell particles prepared in Preparation Example 5, 0.04 parts of sodium 2-hydroxy-3-(4-benzoylphenoxy)propanesulfonate, and 340 parts of deionized water; The preparation method of the magnetic graphene-based composite material for degrading dyes comprises the following steps: Functionalized graphene oxide was ultrasonically dispersed in deionized water, the ultrasonic frequency was controlled to be 30kHz, the ultrasonic power was 450w, the ultrasonic time was 20min, and the temperature was raised to 65°C while stirring at a speed of 600rpm. Then, thiolated core-shell particles and sodium 2-hydroxy-3-(4-benzoylphenoxy)propanesulfonate were added, the speed was maintained unchanged, and stirring was continued for 14min until uniform, and then placed in a 365nm wavelength peak and 80mw / cm 2 The mixture was irradiated under ultraviolet light for 15 minutes, the rotary evaporation temperature was controlled to be 55°C, the deionized water was removed by rotary evaporation, the mixture was washed with deionized water for 4 times, and the mixture was dried at 65°C to constant weight to obtain a magnetic graphene-based composite material for dye degradation.

[0028] Example 3 This embodiment provides a magnetic graphene-based composite material for degrading dyes, comprising the following raw materials in parts by weight: 44 parts of functionalized graphene oxide prepared in Preparation Example 3, 8 parts of thiolated core-shell particles prepared in Preparation Example 6, 0.06 parts of sodium 2-hydroxy-3-(4-benzoylphenoxy)propanesulfonate, and 360 parts of deionized water; The preparation method of the magnetic graphene-based composite material for degrading dyes comprises the following steps: Functionalized graphene oxide was ultrasonically dispersed in deionized water, the ultrasonic frequency was controlled to be 25kHz, the ultrasonic power was 400w, the ultrasonic time was 24min, the temperature was raised to 70°C while stirring at a speed of 650rpm, and then thiolated core-shell particles and sodium 2-hydroxy-3-(4-benzoylphenoxy)propanesulfonate were added, the speed was maintained unchanged, stirring was continued for 16min until uniform, and then placed at a wavelength peak of 365nm and an intensity of 80mw / cm 2 The mixture was irradiated under ultraviolet light for 20 minutes, the rotary evaporation temperature was controlled to be 60°C, the deionized water was removed by rotary evaporation, the mixture was washed with deionized water for 5 times, and the mixture was dried at 70°C to constant weight to obtain a magnetic graphene-based composite material for dye degradation.

[0029] Comparative Example 1 This comparative example provides a magnetic graphene-based composite material for degrading dyes, comprising the following raw materials in parts by weight: 36 parts of functionalized graphene oxide prepared in comparative preparation example 1, 6 parts of thiolated core-shell particles prepared in preparation example 4, 0.02 parts of sodium 2-hydroxy-3-(4-benzoylphenoxy)propanesulfonate, and 320 parts of deionized water; The preparation method of the magnetic graphene-based composite material for degrading dyes comprises the following steps: Functionalized graphene oxide was ultrasonically dispersed in deionized water, the ultrasonic frequency was controlled to be 35kHz, the ultrasonic power was 500w, the ultrasonic time was 16min, and the temperature was raised to 60°C while stirring at a speed of 550rpm. Then, thiolated core-shell particles and sodium 2-hydroxy-3-(4-benzoylphenoxy)propanesulfonate were added, the speed was maintained unchanged, and stirring was continued for 12min until uniform, and then placed at a wavelength peak of 365nm and an intensity of 80mw / cm 2 The mixture was placed under ultraviolet light for 10 min, the rotary evaporation temperature was controlled to be 50°C, the deionized water was removed by rotary evaporation, the mixture was washed with deionized water for 3 times, and the mixture was dried at 60°C to constant weight to obtain a magnetic graphene-based composite material for dye degradation.

[0030] Comparative Example 2 This comparative example provides a magnetic graphene-based composite material for degrading dyes, comprising the following raw materials in parts by weight: 36 parts of functionalized graphene oxide prepared in comparative preparation example 2, 6 parts of thiolated core-shell particles prepared in preparation example 4, 0.02 parts of sodium 2-hydroxy-3-(4-benzoylphenoxy)propanesulfonate, and 320 parts of deionized water; The preparation method of the magnetic graphene-based composite material for degrading dyes comprises the following steps: Functionalized graphene oxide was ultrasonically dispersed in deionized water, the ultrasonic frequency was controlled to be 35kHz, the ultrasonic power was 500w, the ultrasonic time was 16min, and the temperature was raised to 60°C while stirring at a speed of 550rpm. Then, thiolated core-shell particles and sodium 2-hydroxy-3-(4-benzoylphenoxy)propanesulfonate were added, the speed was maintained unchanged, and stirring was continued for 12min until uniform, and then placed at a wavelength peak of 365nm and an intensity of 80mw / cm 2 The mixture was placed under ultraviolet light for 10 min, the rotary evaporation temperature was controlled to be 50°C, the deionized water was removed by rotary evaporation, the mixture was washed with deionized water for 3 times, and the mixture was dried at 60°C to constant weight to obtain a magnetic graphene-based composite material for dye degradation.

[0031] Comparative Example 3 This comparative example provides a magnetic graphene-based composite material for degrading dyes, comprising the following raw materials in parts by weight: 36 parts of functionalized graphene oxide prepared in Preparation Example 1, 6 parts of thiolated core-shell particles prepared in Comparative Preparation Example 3, 0.02 parts of sodium 2-hydroxy-3-(4-benzoylphenoxy)propanesulfonate, and 320 parts of deionized water; The preparation method of the magnetic graphene-based composite material for degrading dyes comprises the following steps: Functionalized graphene oxide was ultrasonically dispersed in deionized water, the ultrasonic frequency was controlled to be 35kHz, the ultrasonic power was 500w, the ultrasonic time was 16min, and the temperature was raised to 60°C while stirring at a speed of 550rpm. Then, thiolated core-shell particles and sodium 2-hydroxy-3-(4-benzoylphenoxy)propanesulfonate were added, the speed was maintained unchanged, and stirring was continued for 12min until uniform, and then placed at a wavelength peak of 365nm and an intensity of 80mw / cm 2 The mixture was placed under ultraviolet light for 10 min, the rotary evaporation temperature was controlled to be 50°C, the deionized water was removed by rotary evaporation, the mixture was washed with deionized water for 3 times, and the mixture was dried at 60°C to constant weight to obtain a magnetic graphene-based composite material for dye degradation.

[0032] Comparative Example 4 This comparative example provides a magnetic graphene-based composite material for degrading dyes, comprising the following raw materials in parts by weight: 36 parts of functionalized graphene oxide prepared in Preparation Example 1, 6 parts of thiolated core-shell particles prepared in Comparative Preparation Example 4, 0.02 parts of sodium 2-hydroxy-3-(4-benzoylphenoxy)propanesulfonate, and 320 parts of deionized water; The preparation method of the magnetic graphene-based composite material for degrading dyes comprises the following steps: Functionalized graphene oxide was ultrasonically dispersed in deionized water, the ultrasonic frequency was controlled to be 35kHz, the ultrasonic power was 500w, the ultrasonic time was 16min, and the temperature was raised to 60°C while stirring at a speed of 550rpm. Then, thiolated core-shell particles and sodium 2-hydroxy-3-(4-benzoylphenoxy)propanesulfonate were added, the speed was maintained unchanged, and stirring was continued for 12min until uniform, and then placed at a wavelength peak of 365nm and an intensity of 80mw / cm 2 The mixture was placed under ultraviolet light for 10 min, the rotary evaporation temperature was controlled to be 50°C, the deionized water was removed by rotary evaporation, the mixture was washed with deionized water for 3 times, and the mixture was dried at 60°C to constant weight to obtain a magnetic graphene-based composite material for dye degradation.

[0033] Performance Testing Performance Testing Adsorption performance: Taking methylene blue solution as an example, the adsorption and degradation performance of the magnetic graphene-based composite material for degrading dyes prepared in the present application was simulated.

[0034] Add 200 mL of a 50 mg / L methylene blue solution to a reaction tube, add 0.5 g of the magnetic graphene-based composite material for dye degradation prepared in Examples 1-4 and Comparative Examples 1-3 as a catalyst, place in a dark place and stir for 0.5 h, test the concentration of the reaction solution, calculate the adsorption rate, then place in a photocatalytic reactor, introduce a constant flow of air, use a 300 W high-pressure mercury lamp as an ultraviolet light source, the wavelength of the light is 365 nm, and the vertical distance between the light source and the solution is 10 cm. After the photoreaction, remove 5 mL of the dispersion from the reaction system every 30 minutes and place in a centrifuge tube, take the upper clear liquid, use a U3900 ultraviolet-visible spectrophotometer to test the absorbance and concentration of methylene blue in the solution, and calculate the degradation rate after treatment. The degradation rate calculation formula is shown in formula (1); (1) Where D is the degradation rate, C 0 , C, A 0 , A represents the initial concentration and concentration after treatment, initial absorbance and absorbance after treatment of the solution, respectively. The test results are shown in Table 1; Table 1 Adsorption and degradation performance test of graphene-based composite materials prepared in Examples 1-3 and Comparative Examples 1-4

[0035] It can be seen from Table 1 that, compared with Comparative Examples 1-4, the graphene-based composite materials for degrading dyes prepared in Examples 1-3 have more excellent adsorption and degradation performance.

[0036] 2. Antibacterial properties Antibacterial rate: Escherichia coli and Staphylococcus aureus were used as bacterial models. The antibacterial rate of the adsorbent material after 5 uses was detected by the number of bacteria in the culture medium using the oscillation method. The test results are shown in Table 2: Table 2 Antibacterial performance test of graphene-based composite materials prepared in Examples 1-3 and Comparative Examples 1-4

[0037] It can be seen from Table 2 that, compared with Comparative Examples 1-4, the magnetic graphene-based composite materials for degrading dyes prepared in Examples 1-3 have more excellent antibacterial properties.

[0038] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A magnetic graphene-based composite material for degrading dyes, characterized in that: The method comprises the following raw materials in parts by weight: 36-44 parts of functionalized graphene oxide, 6-8 parts of thiol core-shell particles, 0.02-0.06 parts of photoinitiator and 320-360 parts of deionized water; The functionalized graphene oxide is firstly prepared by amidation reaction of maleic acid and aniline to obtain an unsaturated monomer, which is then further amidated with graphene oxide to obtain modified graphene oxide, and finally amidated with chitosan to obtain the functionalized graphene oxide. The thiolated core-shell particles are first prepared from nano-magnetic ferroferric oxide, hexadecyltrimethylammonium bromide, tetrabutyl titanate, anhydrous ethanol and deionized water by a sol-gel method to obtain a mixed solution c, which is then subjected to heat treatment to obtain thiolated core-shell particles, which are then modified with KH-560 and finally prepared by a ring-opening esterification reaction with 2-mercaptonicotinic acid.

2. The magnetic graphene-based composite material for degrading dyes according to claim 1, characterized in that: The functionalized graphene oxide is prepared by the following steps: Step A1, adding butenedioic acid to anhydrous ethanol, heating to 40-46° C., stirring evenly, then adding a mixed solution a of N,N'-dicyclohexylcarbodiimide, 4-dimethylaminopyridine, aniline and anhydrous ethanol, heating to reflux, stirring to react for 4-6 hours, and after the reaction is completed, centrifuging, washing the precipitate, and drying to obtain an unsaturated monomer; Step A2, mixing graphene oxide and deionized water, and ultrasonically dispersing to obtain a graphene oxide suspension; at room temperature, adjusting the pH value to 8-9, and dripping a mixed solution b of an unsaturated monomer and anhydrous DMF, and controlling the dripping to be completed within 15 minutes. After the dripping is completed, the temperature is raised to 75-85° C. under a nitrogen atmosphere, the speed is maintained unchanged, and the reaction is stirred for 10-20 minutes, filtered, washed, and dried to obtain modified graphene oxide; Step A3, chitosan, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide are added to an acetic acid aqueous solution, stirred evenly, and then the modified graphene oxide aqueous solution is added, the temperature is raised to 54-66° C., stirred for reaction for 1-2 hours, cooled to room temperature, the pH value is adjusted to neutral, the reduced pressure is filtered, washed, and dried to obtain functionalized graphene oxide.

3. The magnetic graphene-based composite material for degrading dyes according to claim 2, characterized in that: In the step A1, the mass ratio of maleic acid, anhydrous ethanol and mixed solution a is 2-4:46-54:22-28, and in the mixed solution a, the mass ratio of N,N'-dicyclohexylcarbodiimide, 4-dimethylaminopyridine, aniline and anhydrous ethanol is 4-7:3-5:1.5-3.1:

32.

4. The magnetic graphene-based composite material for degrading dyes according to claim 2, characterized in that: In the step A2, the mass ratio of graphene oxide to deionized water is 1:100, the mass ratio of graphene oxide suspension to mixed solution b is 20-30:14-16, and in the mixed solution b, the mass ratio of unsaturated monomer to anhydrous DMF is 3-5:

20.

5. The magnetic graphene-based composite material for degrading dyes according to claim 2, characterized in that: In the step A3, the mass ratio of chitosan, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, N-hydroxysuccinimide, acetic acid aqueous solution and modified graphene oxide aqueous solution is 0.6:3-4:2.6-3.0:25-35:46-52, the modified graphene oxide aqueous solution is obtained by ultrasonically dispersing the modified graphene oxide and deionized water in a mass ratio of 1:10, and the mass fraction of the acetic acid aqueous solution is 0.6-1%.

6. The magnetic graphene-based composite material for degrading dyes according to claim 1, characterized in that: The thiol core-shell particles are prepared by the following steps: Step B1, ultrasonically dispersing nano-magnetic ferroferric oxide into anhydrous ethanol, dripping a mixture of tetrabutyl titanate, hexadecyltrimethylammonium bromide, anhydrous ethanol and deionized water c, and controlling the dripping to be completed within 10 minutes. After the dripping is completed, adjusting the pH to 2-3, heating to 44-52° C., keeping warm and stirring for 18-22 minutes, then heating to reflux, stirring and reacting for 6-8 hours, to obtain modified core-shell particles; Step B2, ultrasonically mix the modified core-shell particles, deionized water, anhydrous ethanol and KH-560 for 20-30 minutes, stir and react at room temperature for 6-8 hours, centrifuge, wash and dry the precipitate to obtain epoxy core-shell particles, ultrasonically disperse the epoxy core-shell particles and anhydrous DMF, dropwise add a mixed solution d of tetrabutylammonium bromide, 2-mercaptonicotinic acid and anhydrous DMF, and after the addition is completed, heat to 105-115° C. and stir for 2-3 hours. After the reaction is completed, centrifuge, wash and dry the precipitate to obtain thiolated core-shell particles.

7. The magnetic graphene-based composite material for degrading dyes according to claim 6, characterized in that: In the step B1, the mass ratio of nano-magnetic ferroferric oxide, anhydrous ethanol and mixed solution c is 2.4-3.2:50-60:20-26, and in the mixed solution c, the mass ratio of tetrabutyl titanate, hexadecyltrimethylammonium bromide, anhydrous ethanol and deionized water is 12-14:1:8-10:3-5.

8. The magnetic graphene-based composite material for degrading dyes according to claim 6, characterized in that: In the step B2, the mass ratio of the modified core-shell particles, deionized water, anhydrous ethanol and KH-560 is 3-5:12:30-34:0.4-0.6, the mass ratio of the epoxy core-shell particles, anhydrous DMF and the mixed solution d is 2-4:44-50:14, and in the mixed solution d, the mass ratio of tetrabutylammonium bromide, 2-mercaptonicotinic acid and anhydrous DMF is 0.2:1.2-1.6:

12.

9. A method for preparing a magnetic graphene-based composite material for degrading dyes according to any one of claims 1 to 8, characterized in that: The following steps are involved: Functionalized graphene oxide is ultrasonically dispersed in deionized water, heated to 60-70°C, and then thiol core-shell particles and a photoinitiator are added, stirred evenly, irradiated with ultraviolet light for 10-20 minutes, rotary evaporated, washed, and dried to obtain a magnetic graphene-based composite material for degrading dyes.

Citation Information

Patent Citations

  • Preparation method and application of magnetic graphene oxide adsorbent material

    CN105289515A

  • Oxidized graphene / carboxymethyl chitosan magnetic microsphere adsorbent for adsorbing methyl orange dye and preparation method of adsorbent

    CN105498724A

  • Preparation method and application of magnetic graphene titanium dioxide nano composite wastewater treatment agent

    CN107445387A

  • Preparation and application of chitosan modified magnetic nano material

    CN111458429A

  • Anticorrosive graphene-polyaniline synergistically modified chitosan material and preparation method thereof

    CN112608601A

Cited By

  • Preparation method and application of partially neutralized sodium polyacrylate

    CN120463845A